Measurement of single event effect cross section induced by monoenergetic protons on a 130 nm ASIC. (1st February 2022) - Boumediene, D.; Jouve, F.; Lambert, D.; Madar, R.; Manen, S.; Perrin, O.; Royer, L.; Soulier, A.; Vandaele, R.
Abstract: Designing integrated circuits in radiation environments such as the High Luminosity LHC (HL-LHC) is challenging. Integrated circuits will be exposed to radiation-induced Single Event Effects (SEE). In deep sub-micron technology devices, the impact of SEEs can be mitigated by triple modular redundancy. The triplication of the most sensitive data is used to recover most of the data corruption induced by interacting particles. One type of SEE, called single event upset (SEU), is studied in this paper. The SEU cross-section and the performance of the triplication are estimated using an ASIC prototype exposed to a beam of protons. The SEU cross-section is measured and systematic difference between 1→0 and 0→1 bit flip rates is observed. The efficiency of the mitigation method is investigated.